Feminization, construction and re-construction of madness: intertextuality between Jane Eyre and Wide Sargasso Sea - Jalali, Jamila (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.